Bali Folktale I Belog Oriented Towards Postmodernism to Increase Curiosity in Elementary School Students - I Kadek Baladiva Anggarana; Putu Nanci Riastini; Ni Ketut Desia Tristiantari (Journal for Lesson and Learning Studies, 2026)
The research problem focuses on the low level of curiosity among elementary school students and the limited availability of local culture-based learning resources as reading materials that can stimulate students' curiosity. This study aims to produce a remake of the Satua Bali I Belog storybook with a postmodernist orientation and to test the validity and user response to the storybook as a learning resource. This study uses the ADDIE development model, which includes the stages of analysis, design, development, and evaluation. The subject of this study is the remake of the Satua Bali I Belog storybook, which is adapted to the daily lives of elementary school students today. The feasibility of the product is reviewed based on content validity and user response to the storybook. Data were collected through a relevance scale for subject matter and media validity, as well as a questionnaire for user response involving teachers and students. The results of the study showed content validity with a very high qualification, as indicated by the content expert and media expert validity index of 1.00. The teacher response was 97% and the student response was 97.67%. These findings indicate that the Satua Bali I Belog storybook developed is suitable for use as a learning resource and reading material to foster curiosity in elementary school students.